Writing behavior, strategies and styles National Defence University: a contrastive rhetoric study of three ethnic groups / Abdul Rahim Abdul Rahman - Abdul Rahman, Abdul Rahim (2013)
The thinking processes, verbalization and writing text could provide coherent and clear understanding on language, psychology and communication processes relationship within a diverse multicultural setting such as Malaysia. It started with Kaplan (1966) who introduced contrastive rhetoric concept in a seminal paper that studied hundreds of essays produced by his foreign students who are studying in the States universities and he introduced five doodles that represent five ethnic groups when communicating in English writing. In this study, in honoring the views proposed by Kaplan (1966) and Connors (1996), this study incorporated writing behavior, writing strategies and writing styles as the centerfold of the ESL writing study conducted at National Defence University, Malaysia. Three respondents that represent three main ethnic groups in Malaysia are selected as the writers of this study. The respondents’ ethnics groups are the Malay, Malaysian of Chinese Descendants and Malaysian of Indian Descendants. In order to analyze that different culture affected the English writing, Hayes (1996) writing model was selected as the conceptual framework in collecting the data of this study. With Hayes (1996), this research can be conducted by assigning respondents with collaborators that come from the same ethnic groups of which the model acknowledged. This concurs with the aim of this study that analyzes the differences between individuals who come from different ethnic background when writing English essay. The instruments used in understanding this study are Narrative Inquiry (NI) notes, Thinking Aloud Protocols (TAP) transcripts and the Text Produced So Far (TPSF) writing text. It was found that the individual differences emerged though1 generalization is not permitted. This study is successful in determining that there are differences in term of writing behavior, strategies and styles with the aid of the introduction of the contrastive rhetoric tree as the centerfold concept of this research. At the end, this study summarized that each individual in an ethnic groups is as ‘a tree in a forest’ and with that concept, the EL officers instructor and instructors in the Malaysian Armed Forces (MAF) would benefited the concept of ‘knowing the individual tree in a forest’ as opposed to ‘knowing the forest, you know the trees’ concept that as the preferred methodology in planning their English writing class.